(untitled) (Palíndromo, 2013)
The collection of woodcuts that compose Antonio Dias’ Trama is exposed as a semi-rectangular panel, that alludes to The Illustration of Art (1972-77) series. The prints expose some graphic structures taken from his “diagram-paintings” series, made between 1968-71. In each print there is a different written proposition, forming several "floorplans”, that propose to erect a series of impossible geometric "monuments" – related, in a way, to the participatory dimension of H.Oiticica’s “environmental art”. Are those prints proposals for future action or descriptions of an experienced place? By interposing historical materials from the Brazilian artistic debate (pieces of geometry from the national-developmentalist period of the 50’s and the "participation of the spectator" from the cultural resistance of the 60’s), Trama operates an assemblage of historical time, which implies a new temporality – filled with that Jetztzeit described by Walter Benjamin: the open temporality of infinite possibilities promised by the social revolution.